How Does Income Inequality Impact Economic Growth in the United States? (International Journal of Applied Research in Management and Economics, 2025)
This paper aims to examine the effect of income inequality on economic growth in the United States at the county level, using linear regression models to analyze the data from 2010 and 2019. Since income inequality has significantly increased in recent years, understanding its impact on economic growth, specifically through median household income, has become essential for policymakers and economists. Through statistical analysis, using linear regression of median income on the Gini index with an instrumental variable of economic connectedness, a significant causation between income inequality and economic growth was found, suggesting that higher levels of inequality can impede overall economic progress. According to the results, a 0.01 rise in the Gini coefficient results in a 12,590 dollar drop in median income for 2010 and in a 48,858 dollar drop in median income for 2019. However, only the results for 2010 are statistically significant. This might suggest that the impact of income inequality on median income is decreasing.